Talking about food : the social and global in eating communities - Rüdiger, Sofia; Muehleisen, Susanne (Impact, studies in language and society, 2020)
"All humans eat and all humans speak - activities which in social life often, but not always, co-occur: We talk while eating and drinking with others, but food is also a prominent literal and metaphorical discursive topic which contributes to establishing communities and identities. This omnipresence of eating and drinking in our daily lives has led to a public fascination with foodways. The contributions in this edited collection investigate the connection between language and food from a variety of perspectives. As food discourses operate on local, global, and mediated levels, they are intertwined with notions of identity and culture and thus shed light on intimate understandings of ourselves as human beings. Talking about Food - The Social and the Global in Eating Communities provides up-to-date and thought-provoking contributions to the linguistics of food. The book is essential reading for anyone interested in food-related subjects"--